Impact of hyperprolactinemia in a patient with polyautoimmunity (2019)
Hyperprolactinemia has been proposed as a triggering factor for autoimmune diseases. The increased levels of prolactin could induce an abnormal immune response. Herein, we present a patient with hyperprolactinemia who developed polyautoimmunity. Patient's symptoms were associated with slightly raised levels of prolactin (20-40 ng/mL) and administration of dopaminergic agonists. © 2018 The Authors. Clinical Case Reports published by John Wiley and Sons Ltd.